The social management of medical ethics in sport: confidentiality in English professional football - Waddington, I.; Scott-Bell, A.; Malcolm, D. (International Review for the Sociology of Sport, 2019)
This paper examines one of the major ethical challenges in the practice of sports medicine, confidentiality. Drawing on interview and questionnaire data with doctors and physiotherapists working in English professional football clubs, it explores the degree to which ethical compliance has improved since the publication of, and publicity surrounding, an earlier study of medical practice in professional football conducted by Waddington and Roderick. Thus, it provides an updated empirical examination of the management of medical ethics in sport. The data illustrate how the physical and social environmental constraints of sports medicine practice impinge upon the protection of athlete-patient confidentiality, how ethical codes and conflicting obligations converge to shape clinician behaviour in relation to lifestyle and injury issues, and the ethically problematic contractual constraints under which clinicians and athletes operate. It demonstrates that medical ethical practice continues to be very variable and draws on Freidson`s work on medical `work settings` to argue that there is a need to augment existing confidentiality policies with more structurally oriented approaches to ensure both professional autonomy and medical ethical compliance in sport.